2006
DOI: 10.1093/ps/85.11.1900
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Oxidative Burst and Degranulation in Chicken Heterophils Stimulated with Probiotic Bacteria

Abstract: The immune system of neonatal chicks is functionally immature during the first week of life. Researchers have previously demonstrated that the avian humoral response can be increased with probiotics. Although the humoral response provides the chick with an effective mechanism to combat pathogens, sufficient antibody titers are not attained until 7 to 10 d postinfection. However, the innate immune system (i.e., heterophils) can respond much more quickly to pathogens. The objective of this study was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…Most of probiotics benefit the host by immune regulation, particularly through the balanced control of pro-inflammatory and anti-inflammatory cytokines (Li et al, 2009;Foligne et al, 2010;Jobin, 2010). Several studies have provided unequivocal evidence that certain probiotics strains are able to stimulate several aspects of innate (Farnell et al, 2006;Boirivant et al, 2008;Romanin et al, 2010;Weiss et al, 2010) and humoral immunity (Galdeano et al, 2009). Moreover, the extracellular enzymes produced by Bacillus subtilis may boost the general gut immune function (Chen et al, 2009).…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…Most of probiotics benefit the host by immune regulation, particularly through the balanced control of pro-inflammatory and anti-inflammatory cytokines (Li et al, 2009;Foligne et al, 2010;Jobin, 2010). Several studies have provided unequivocal evidence that certain probiotics strains are able to stimulate several aspects of innate (Farnell et al, 2006;Boirivant et al, 2008;Romanin et al, 2010;Weiss et al, 2010) and humoral immunity (Galdeano et al, 2009). Moreover, the extracellular enzymes produced by Bacillus subtilis may boost the general gut immune function (Chen et al, 2009).…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…Balanced gastrointestinal microflora and immune-stimulation or regulation of cell mediated or humoral immunity are major functional effects attributed to the consumption of probiotics [18,26,[32][33][34][35][36]. However, several animal and human studies have provided unequivocal evidence that specific strains of probiotics are able to stimulate multiple aspects of innate immunity [3,8,20,[37][38][39][40]. The importance of the intestinal microflora composition in physiological and pathophysiological processes in the GIT, is becoming more evident and has led to new possibilities for prevention and therapy of diseases [4,18,41].…”
Section: Mechanism Of Action Of Probioticsmentioning
confidence: 99%
“…Extensive laboratory and field research conducted with this defined LAB culture has demonstrated accelerated development of normal microflora in chickens and turkeys, providing increased resistance to Salmonella spp. infections [37,[67][68][69][70][71][72]. Published experimental and commercial studies have shown that these selected probiotic organisms are able to reduce idiopathic diarrhea in commercial turkey brooding houses [73].…”
Section: Probiotics In Poultry Researchmentioning
confidence: 99%
“…The immune system of the neonatal chick is immature and inefficient during the first week of life, rendering the bird extremely vulnerable to infectious threats found in the environment [1]. Immunomodulators are currently being studied and sought after to counteract the inadequacies of the chick immune system and promote host defense during this immunologically liable time.…”
Section: Introductionmentioning
confidence: 99%